2001
DOI: 10.1002/jmv.1047
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the quantitative antigenemia assay and the cobas amplicor monitor quantitative PCR assay for detecting CMV viraemia in bone marrow and solid organ transplant patients

Abstract: The relationship between quantitative PCR (COBAS Amplicor CMV Monitor, Roche Diagnostics) and quantitative antigenemia (Monofluor pp65, Sanofi Diagnostics) was examined for monitoring CMV viraemia. A total of 469 specimens from immunocompromised haematology and solid organ transplant patients were tested by quantitative antigenemia and qualitative PCR. Quantitative PCR (QPCR) was performed on the 245 specimens in which CMV DNA was detected by qualitative PCR. To exclude any effect due to specific anti-CMV trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Five studies found CMV DNA PCR monitoring (qualitative or quantitative) to be more sensitive than Ag assay, irrespective of performance with plasma, PBL, or WB (26,40,76,89,93). In only one report were leukocyte-based assays (Ag and PBL PCR assays) more sensitive than a plasma PCR, showing a higher number of patients with CMV reactivation, earlier positivity, and a more rapid decrease of viral load after the start of preemptive antiviral therapy (9).…”
Section: Cobas Amplicor CMV Dna (Monitor) Testmentioning
confidence: 99%
“…Five studies found CMV DNA PCR monitoring (qualitative or quantitative) to be more sensitive than Ag assay, irrespective of performance with plasma, PBL, or WB (26,40,76,89,93). In only one report were leukocyte-based assays (Ag and PBL PCR assays) more sensitive than a plasma PCR, showing a higher number of patients with CMV reactivation, earlier positivity, and a more rapid decrease of viral load after the start of preemptive antiviral therapy (9).…”
Section: Cobas Amplicor CMV Dna (Monitor) Testmentioning
confidence: 99%
“…Although quantitative PCR methods are widely used in CMV diagnostics, the clinical correlation of the findings is not as clear as that with the pp65 assay. High viral loads, measured by quantitative DNA-PCR methods, have been shown to correlate with the appearance of symptomatic CMV infection in a similar way (3,4,7,12,17,21,24). As the tendency nowadays is towards replacement of the pp65 assay with PCR methods, the clinical use of these methods should be evaluated in parallel, not only in the diagnosis of CMV infection but also in the monitoring of individual transplant patients during an active infection.…”
mentioning
confidence: 92%
“…In fact, discrepant results have been published on this subject. (1,4,6,9,10,19,21,27,31,35,38,39,40). Recent data on the performance of several highly sensitive real-time PCRs, both laboratory-developed and commercial assays (5,20,22), however, demonstrate that both plasma and whole blood are equally suitable for monitoring active CMV infection in Allo-SCT recipients.…”
mentioning
confidence: 99%